Patients submitted to Morton neuroma’s neurectomy for plantar digital nerve through plantar approach: retrospective clinical evaluation of surgical results - Pereira de Sá, Lucas; Nunes, Lerud Frosi; Ramalho, Ricardo Borges; Zeferino, Vinicius Andretti; Barroso, Bernardo Garcia; Kriger, Jorge Luiz (Journal of the Foot & Ankle, 2023)
Objectives: Evaluate postoperative clinical outcomes of patients submitted to neurectomy to treat plantar digital nerve neuroma through plantar approach with a minimum of 12 months postoperative. Methods: Patients submitted to neurectomy through plantar approach between 2011 and 2020 were evaluated. Twenty-eight patients were included, and 29 feet were operated on, totaling 35 resected neuromas. The medical records were evaluated, and the participants answered a form containing questions about the parameters of the Clinical Evaluation for Interdigital Neuroma and classified according to a visual analog pain scale. Results: A predominance of females (85.71%) was observed, with a mean age of 51.55 at the surgery date. The left side was predominant (62.06%). The most affected intermetatarsal space was the third (77.14%). Clinical evolution was “excellent” (58.62%), “good” (13.79%), “fair” (20.68%), and “poor” (6.89%). A mean of 1.79 corresponding to “mild” was demonstrated. Conclusion: The patients presented “good” clinical evolution, low pain level, and high patient satisfaction rate after a mean of 34.79 months after surgery